2019
DOI: 10.1007/s13361-019-02296-2
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study to Identify the Drug Conjugation Site of a Site-Specific Antibody-Drug-Conjugate Using Middle-Down Mass Spectrometry

Abstract: Middle-down mass spectrometry (MD MS) has emerged as a promising alternative to classical bottom-up approaches for protein characterization. Middle level experiments after enzymatic digestion are routinely used for subunit analysis of monoclonal antibody (mAb)-related compounds, providing information on drug load distribution and average drug-to-antibody ratio (DAR). However, peptide mapping is still the gold standard for primary amino acid sequence assessment, post-translational modifications (PTM) and drug c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…The characterization of antibody subunits by tandem mass spectrometry (MS/MS), typically coupled with reversed phase liquid chromatography, has been extensively explored. ,, Multiple MS/MS methods, including combinations of 213 and 193 nm ultraviolet photodissociation (UVPD), electron-transfer dissociation (ETD), collisionally activated dissociation (CAD), higher-energy collisional dissociation (HCD), electron capture dissociation (ECD), and hybrid ETD/HCD (EThcD), have been used to enhance characterization, with coverages of 50–80% typically reported. ,,, Fraction collection of subunits followed by MALDI-insource decay has also been utilized to obtain sequence coverages as high as 90% for each subunit. , While many MS1-based top-down and middle-level characterization methods for ADCs have been developed, , MS/MS analysis of ADCs is still in the early stages of development. Two recent studies have demonstrated the initial application of middle-down MS/MS strategies for the analysis of ADC subunits. , One expansive study reported the use of ETD to effectively identify payload locations on heterogeneous antibodies by focusing on specific diagnostic fragment ions, even attaining localization of conjugation sites of positional isomers as well as oxidation sites . Another investigation compared ETD, 213 nm UVPD, and HCD for analysis of a next-generation ADC .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The characterization of antibody subunits by tandem mass spectrometry (MS/MS), typically coupled with reversed phase liquid chromatography, has been extensively explored. ,, Multiple MS/MS methods, including combinations of 213 and 193 nm ultraviolet photodissociation (UVPD), electron-transfer dissociation (ETD), collisionally activated dissociation (CAD), higher-energy collisional dissociation (HCD), electron capture dissociation (ECD), and hybrid ETD/HCD (EThcD), have been used to enhance characterization, with coverages of 50–80% typically reported. ,,, Fraction collection of subunits followed by MALDI-insource decay has also been utilized to obtain sequence coverages as high as 90% for each subunit. , While many MS1-based top-down and middle-level characterization methods for ADCs have been developed, , MS/MS analysis of ADCs is still in the early stages of development. Two recent studies have demonstrated the initial application of middle-down MS/MS strategies for the analysis of ADC subunits. , One expansive study reported the use of ETD to effectively identify payload locations on heterogeneous antibodies by focusing on specific diagnostic fragment ions, even attaining localization of conjugation sites of positional isomers as well as oxidation sites . Another investigation compared ETD, 213 nm UVPD, and HCD for analysis of a next-generation ADC .…”
mentioning
confidence: 99%
“…Two recent studies have demonstrated the initial application of middle-down MS/MS strategies for the analysis of ADC subunits. , One expansive study reported the use of ETD to effectively identify payload locations on heterogeneous antibodies by focusing on specific diagnostic fragment ions, even attaining localization of conjugation sites of positional isomers as well as oxidation sites . Another investigation compared ETD, 213 nm UVPD, and HCD for analysis of a next-generation ADC . For the antibody in this aforementioned study, the payload is fixed on C213 for the Fc/2 subunit and C163 for the Fd′ subunit via modified amino acids .…”
mentioning
confidence: 99%
“…Also, follow-up studies could focus on more targeted topics related to TD/MD MS of mAbs, for example ADC analysis. 105,106…”
Section: Discussionmentioning
confidence: 99%
“…One such application is the study of engineered antibodies which have shown potential to be used as cancer therapies [68]. ETD-based MS methods have been reported in the literature to characterize monoclonal antibodies (mAb) and antibody drug conjugates (ADC) [69][70][71][72][73][74].…”
Section: Fragmentation and Ms Detection Techniquesmentioning
confidence: 99%